1978
DOI: 10.1159/000181438
|View full text |Cite
|
Sign up to set email alerts
|

Middle Molecules Re-Examined

Abstract: Evidence for and against the presence and pathophysiologic importance of middle molecules in uremia is reviewed. The evidence favors both their presence and importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2004
2004

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…As soon as this hypothesis was formulated, and even before the presence of MM had been detected in biological fluids of uremic subjects, great improvements in dialysis techniques were made, due to the search for membranes with greater permeability to substances with a MW of 1.000-2,000 daltons [4,20,23,32,33,43], Dall'Aglio et al [17] showed the accumulation (in sera, urine and dialysis fluids) of components estimated to have a MW lower than 3,500 daltons in uremic patients, using various types of chromatography on Sephadex gels. Dzurik et al [18], without making reference to the MM hypothesis, also isolated, by chromatography of the sera of uremic patients, a toxin with a MW estimated at 1.000-1,500 daltons.…”
Section: Introductionmentioning
confidence: 99%
“…As soon as this hypothesis was formulated, and even before the presence of MM had been detected in biological fluids of uremic subjects, great improvements in dialysis techniques were made, due to the search for membranes with greater permeability to substances with a MW of 1.000-2,000 daltons [4,20,23,32,33,43], Dall'Aglio et al [17] showed the accumulation (in sera, urine and dialysis fluids) of components estimated to have a MW lower than 3,500 daltons in uremic patients, using various types of chromatography on Sephadex gels. Dzurik et al [18], without making reference to the MM hypothesis, also isolated, by chromatography of the sera of uremic patients, a toxin with a MW estimated at 1.000-1,500 daltons.…”
Section: Introductionmentioning
confidence: 99%